Predictors of Significant Worsening of Patient-Reported Fatigue over a One-Month Timeframe in Ambulatory Patients with Common Solid Tumors - Fisch, Michael J. (2013)
PURPOSE: Understanding the determinants of fatigue worsening may help distinguish between different fatigue phenotypes and inform clinical trial designs. PATIENTS AND METHODS: Patients with invasive cancer of the breast, prostate, colon/rectum, or lung were enrolled from multiple sites. At enrollment during an outpatient visit and 4–5 weeks later patients rated their symptoms on a 0–10 numerical rating scale. A 2-point change was considered clinically significant for fatigue change. Effects of demographic and clinical factors on patient-reported fatigue were examined using logistic regression models. RESULTS: 3123 patients were enrolled at baseline and 3032 were analyzable for fatigue change. At baseline, 23% had no fatigue, 35% mild, 25% moderate, and 17% severe. Key parameters in our model of fatigue worsening includes fatigue at baseline (OR 0.75), disease status (OR 1.99), performance status (OR 1.38), history of depression (OR 1.28), patient perception of bother due to comorbidity (OR 1.26) and treatment exposures including recent cancer treatment (OR 1.77), and use of corticosteroids (1.37). The impact of gender was examined only in colorectal and lung cancer patients, and it was a significant factor with men most likely to experience worsening of fatigue (OR=1.46). CONCLUSIONS: Predictors of fatigue worsening include multiple factors that are difficult to modify: baseline fatigue level, gender, disease status, performance status, recent cancer treatment, bother due to comorbidity, and history of depression. Future fatigue prevention and treatment trial designs should account for key predictors of worsening fatigue.